Immune-related adverse events following administration of anti-cytotoxic T-lymphocyte-associated protein-4 drugs: a comprehensive systematic review and meta-analysis - Xu H; Tan P; Zheng X; Huang Y; Lin T; Wei Q; Ai J; Yang L (Dove Medical Press, 2019)
Hang Xu,1,* Ping Tan,1,* Xiaonan Zheng,2,* Yu Huang,1 Tianhai Lin,1 Qiang Wei,1 Jianzhong Ai,1 Lu Yang11Department of Urology, Institute of Urology, West China Hospital, Sichuan University, Chengdu 610041, People’s Republic of China; 2West China Medical School, Sichuan University, Chengdu 610041, People’s Republic of China*These authors contributed equally to this workObjective: Administration of drugs targeting anti-cytotoxic T-lymphocyte-associated protein-4 (CTLA-4) is often associated with serious immune-related adverse events (irAEs). Here, we performed a comprehensive analysis of organ-specific irAEs and treatment-related hematologic abnormalities and musculoskeletal disorders resulting from anti-CTLA-4 treatment.Materials and methods: PubMed, the Cochrane library, Web of Science, and ClinicalTrials.gov were searched for studies between January 1990 and March 2018 reporting AEs associated with anti-CTLA-4 therapies.Results: A total of 11 clinical trials with 7,088 patients were included; of these, data were accessible for 10 on ClinicalTrials.gov. Compared with control therapies (placebo, chemotherapy, radiation therapy, or vaccine), anti-CTLA-4 therapies (ipilimumab and tremelimumab) were associated with an increased risk of serious irAEs, predominantly dermatologic (rash: odds ratio [OR] 3.39, P<0.01), gastrointestinal (diarrhea and colitis: OR 6.57 and 14.01, respectively; both P<0.001), endocrine (hypophysitis, hypothyroidism, adrenal insufficiency, and hypopituitarism: OR 4.22, 3.72, 3.77, and 4.73, respectively; all P<0.05), and hepatic (hepatitis, elevated alanine aminotransferase, and elevated aspartate aminotransferase: OR 4.44, 3.28, and 3.12, respectively; all P<0.05). The most common serious organ-specific irAEs were gastrointestinal (diarrhea 9.8% and colitis 5.3%). Although the incidence of selected events was higher in anti-CTLA-4-treated patients, no significant differences were found between anti-CTLA-4 and the control therapies in treatment-related hematologic abnormalities or severe musculoskeletal disorders.Conclusion: Anti-CTLA-4 therapies are associated with an increased risk of serious organ-specific irAEs, most frequently involving the gastrointestinal system; however, no increased risk of hematologic abnormalities or severe musculoskeletal disorders was detected compared with other therapies. These results underscore the need for clinical awareness and prompt and effective management of multi-organ irAEs related to anti-CTLA-4 drugs.Keywords: immune-related adverse events, anti-CTLA-4 drugs, ipilimumab, tremelimumab